Computational biology and in vitro studies for anticipating cancer-related molecular targets of sweet wormwood (Artemisia annua) - Hend Dawood; Ismail Celik; Reham S. Ibrahim (BMC, 2023)
Abstract Background Cancer is one of the leading causes of death worldwide. Recently, it was shown that many natural extracts have positive effects against cancer, compared with chemotherapy or recent hormonal treatments. A. annua is an annual medicinal herb used in the traditional Chinese medicine. It has also been shown to inhibit the proliferation of various cancer cell lines. Methods Multi-level modes of action of A. annua constituents in cancer therapy were investigated using an integrated approach of network pharmacology, molecular docking, dynamic simulations and in-vitro cytotoxicity testing on both healthy and cancer cells. Results Network pharmacology-based analysis showed that the hit Artemisia annua constituents related to cancer targets were 3-(2-methylpropanoyl)-4-cadinene-3,11-diol, artemisinin G, O-(2-propenal) coniferaldehyde, (2-glyceryl)-O-coniferaldehyde and arteamisinin III, whereas the main cancer allied targets were NFKB1, MAP2K1 and AR. Sixty-eight significant signaling KEGG pathways with p < 0.01 were recognized, the most enriched of which were prostate cancer, breast cancer, melanoma and pancreatic cancer. Thirty-five biological processes were mainly regulated by cancer, involving cellular response to mechanical stimulus, positive regulation of gene expression and transcription. Molecular docking analysis of the top hit compounds against the most enriched target proteins showed that 3-(2-methylpropanoyl)-4-cadinene-3,11-diol and O-(2-propenal) coniferaldehyde exhibited the most stabilized interactions. Molecular dynamics simulations were performed to explain the stability of these two compounds in their protein-ligand complexes. Finally, confirmation of the potential anticancer activity was attained by in-vitro cytotoxicity testing of the extract on human prostate (PC-3), breast (MDA-MB-231), pancreatic (PANC-1) and melanoma (A375) cancerous cell lines. Conclusion This study presents deeper insights into A. annua molecular mechanisms of action in cancer for the first time using an integrated approaches verifying the herb's value.